11 Tiger versus judkins diagnostic catheters in trans-radial coronary angiography. (October 2018) - Cadogan, D; O'Hare, D; Murphy, L; Mubarak, S; McCreery, C
Abstract : Aims: To retrospectively compare performance outcomes and cost with use of Tiger versus Judkins diagnostic catheters in trans -radial diagnostic coronary angiography. Methods: The hospital's electronic database was used to review diagnostic coronary angiograms performed by four cardiology registrars, each acting as first operator under consultant supervision. Fifty-four days were reviewed between 16/10/17 and 23/4/18. First-choice catheter(s) used were reviewed and performance outcomes assessed were 1) need for additional catheters 2) total Dose Area Product (DAP) 3) total fluoroscopy time 4) contrast volume used 5) duration of catheterisation 6) radial spasm/complications 7) cost. Duration of catheterisation was defined from injection of radial cocktail to recorded case ending/TR band application. Cost was assessed based on net cost of each catheter used. Procedures involving graft studies, fractional-flow reserve, ad-hoc PCI, ventriculography and femoral access were excluded. Results: 373 cases were performed during the study days, of which 217 were eligible for inclusion. 140 were male, 77 female. Mean age was 64.6 years (±12.5). Tiger catheter was first-choice catheter in 135 cases (62.2%), Judkins catheters in 82 cases (37.8%). First-catheter choice size was 5Fr. in 205 cases (94.4%).52 cases (38.5%) in the Tiger group required use of additional catheters. 37 of these required use a single Judkins catheter for case completion and 2 cases required use of non-Judkins catheters. 14 cases (17.1%) in the Judkins cohort required use of additional catheters. 9 of these required a third Judkins catheter for case completion and 4 cases required use of non-Judkins catheters. Mean requirement for additional catheter(s) was lower in the Judkins group (1.26 vs 1.58, p<0.005).Total DAP, fluoroscopy time, contrast volume used and duration of catheterisation were similar between the two groups (Judkins vs Tiger; 2635.9 cGycm2 vs 2704.9cGycm2 (p=0.77), 229 s (±181) vs 229 s (±171) (p=0.96), 63 ml vs 67 ml (p=0.13), 12.9 mins (±5.7) vs 12.6 mins (±6.9) (p=0.68)). Radial spasm was documented in three cases only and was likely underreported. No other complications were encountered. Total average cost of all catheters used was less in the Judkins group (€101.1 vs €112.54 (p=0.024)). Conclusions: Use of Judkins catheters as first choice catheter among cardiology trainees resulted in less requirement for additional catheters and showed significant cost benefit when compared to Tiger catheters. The remaining performance outcomes assessed showed similarity between the two groups. This similarity contradicts recent studies which have shown favour towards Tiger catheters in terms of radiation exposure, contrast volume required and procedure duration.